# SOLUTION: using substitution: x=-y-1 and x-y=-11

Algebra ->  Algebra  -> Coordinate Systems and Linear Equations  -> Lessons -> SOLUTION: using substitution: x=-y-1 and x-y=-11      Log On

 Ad: You enter your algebra equation or inequality - Algebrator solves it step-by-step while providing clear explanations. Free on-line demo . Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help!

 Linear Solvers Practice Answers archive Word Problems Lessons In depth

 Question 620217: using substitution: x=-y-1 and x-y=-11Answer by math-vortex(472)   (Show Source): You can put this solution on YOUR website!Hi, there-- . Use the Substitution method to solve this system of equations: . . Substitute -y-1 for x in the second equation. (We can make this move because the first equation tells us that whatever x is, it is equal to -y-1.) . . Simplify by combining like terms. . Substitute 5 for y in the first equation. . According to our algebra, x=-6 and y=5. Thus the ordered pair (-6,5) is the solution to this system of equations. If you graphed these equations you would see two lines intersecting at (-6,5). . Last step, check the solution in both equations. (It's very east to make an error.) . x=-y-1 (-6)=-(5)-1 -6=-6 Check! . x-y=-11 (-6)-(5)=-11 -11=-11 Check! . Feel free to email me if you still have questions about this. . Ms.Figgy math.in.the.vortex@gmail.com